Stable carbon and oxygen isotopes of benthic Uvigerina spp. in core M78/1_181-3 - Nürnberg, Dirk; Gehre, Nadine; Fessler, Sebastian (PANGAEA, 2025)
The Mississippi River discharge effectively shaped the dynamics of the Loop Current in the Gulf of Mexico during transient climates and interglacials, and reacted in response to changes in sea level and atmospheric circulation. We here provide proxydata records from piston core M78/1-181-3 PC. The ~12 m-long core was recovered from the Mississippi Alabama shelf very close to and southeast of the recent Mississippi delta (29°00.00'N 88°20.00'W) from 804 m water depth during R/V Meteor Cruise M78/1 in 2009 (doi:10.2312/cr_m78_1). The proxyrecords cover the last ~42 kyrs at centennial resolution. Stable oxygen (δ18O, ‰ VPDB) and carbon isotope analyses (δ13C; ‰ VPDB) were performed on the benthic foraminiferal species Uvigerina spp. Sampling and analytical studies were carried out from 3 cm to ~1220 cm core depth at ~5 cm spatial resolution. The stable isotope analyses were run on a Thermo Scientific MAT 253 mass spectrometer with an automated Kiel IV Carbonate Preparation Device at GEOMAR. The isotope data provide stratigraphical and intermediate water information.
Keywords: Gulf of Mexico; Mississippi discharge; Stable isotopes